Protocol format extraction at semantic level - Zheng HONG; Zhen-ji ZHOU; Li-fa WU; Fan PAN (Tongxin xuebao)
Present methods for protocol format extraction analyze the execution traces of programs at syntax level,which leads to redundancy and conflict in the results of fie identification.In order to improve the accuracy of field identifica-tion,a semantic level method was proposed for protocol format extraction.The method firstly translated the binary in-structions into equivalent intermediate language,and tracked the parsing process of field semantics through fine-grained dynamic taint analysis.Further,it extracted otocol format using semantic level policies of field identifica-tion,based on the semantic indivisibility of fields.Experimental results show that the proposed method can achieve high identification accuracy with low complexity.